Application of a Simplified Approach to Link Course Learning Outcomes of Student for Performing Program Assessment and Improvement - Rahim K. Jassim (Research Developments in Science and Technology Vol. 9, 2022)
The most important aspect of any strategy aimed at meeting the objectives of ABET 2000 is the assessment of student results. All of the department’s speciality courses should meet the needed and pre-defined student goals. The attainment of these student outcomes demonstrates that the program objectives were met by the pupils. In this study, a simplified method for assessing the degree of achievement of student outcomes using direct assessment methods is given.